Chiari I Malformation Presenting Vertical Gaze-Evoked Nystagmus : A Case Report: Poster Presentation - Case Report - General practitioner - Mischka Scalvinni Suvero Suyar; Nazhira Janani; Ferdian Ramadhan; Balgis Desy Sulistyowati (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Chiari malformation is characterized by herniation of posterior cerebellar vermis in which type 1 malformation has coexisting syringomyelia of cervicothoracic spinal cord. This malformation can be congenital or acquired, in which gaze-evoked nystagmus is the typical movement deficit. This case aimed to report a case of vertical gaze-evoked nystagmus as a primary symptom to detect Type I Chiari Malformation. Case Illustration : A 44-year-old woman presented with involuntary movements of both eyes in the last 5 months with vision problems in which objects appear to jump or vibrate. Visual acuity was 20/50 in both eyes with 12 prism diopters BI exotropia. We recognized vertical and torsional nystagmus in upgaze without any movement in primary gaze. While performing supraduction, the oscillation was detected and increased. Brain MRI revealed Type I Chiari Malformation. Discussion : Nystagmus was seen in many diseases of the central nervous system, in particular those affecting the brainstem and cerebellum. Vertical gaze evoked nystagmus was a disorder of the gaze holding function, purely vertical gaze-evoked nystagmus is observed in midbrain lesions involving the interstitial nucleus of Cajal (INC) as the neural integrator for vertical gaze-holding function. Based on this pathophysiology, the Brain MRI of this patient revealed some degrees of compression in midbrain, and cervico medullary junction due to her brain malformation. Conclusion : A sustained gaze-evoked nystagmus is an important ocular finding that may indicate serious neurologic pathology. It is important for an eye care provider to thoroughly examine additional tests to determine the underlying cause of the nystagmus.